Cell-extracellular matrix mechanobiology: forceful tools and emerging needs for basic and translational research - Holle, Andrew W.; Young, Jennifer; Spatz, Joachim P. (Nano letters, 2018)
Extracellular biophysical cues have a profound influence on a wide range of cell behaviors, including growth, motility, differentiation, apoptosis, gene expression, adhesion, and signal transduction. Cells not only respond to definitively mechanical cues from the extracellular matrix (ECM) but can also sometimes alter the mechanical properties of the matrix and hence influence subsequent matrix-based cues in both physiological and pathological processes. Interactions between cells and materials in vitro can modify cell phenotype and ECM structure, whether intentionally or inadvertently. Interactions between cell and matrix mechanics in vivo are of particular importance in a wide variety of disorders, including cancer, central nervous system injury, fibrotic diseases, and myocardial infarction. Both the in vitro and in vivo effects of this coupling between mechanics and biology hold important implications for clinical applications.